The Influence Of Mediated Content Marketing and Brand Image electronic Word Of Mouth Regardless Of Interest In Buying Products at Marketplace Tiktok - Yohana Shinta Theresia; Siti Normi; Jeudi Agustina T. P. Sianturi (International Forum of Researchers and Lecturers, 2025)
TikTok Shop is a social e-commerce feature that allows users and creators to promote and sell products while shopping. By selling through TikTok Shop, users and creators can earn money from the platform, especially with the growing number of TikTok users. The presence of the shopping feature on this app makes TikTok increasingly popular because, in addition to entertainment, users do not need to switch to other shopping apps to make transactions. This study aims to examine and analyze the influence of content marketing and brand image mediated by electronic word of mouth (eWOM) on product purchase interest in TikTok Shop. This research uses an associative method with a quantitative approach. The population in this study consists of TikTok Shop consumers in the Dumai area, with an unknown number, categorized as an infinite population. The Lemeshow formula was used for sampling, resulting in 97 respondents. Data analysis was performed using WarpPLS version 8.0 software. Based on the test results, it can be concluded that content marketing has a positive and significant effect on product purchase interest, as well as a positive effect on eWOM. Furthermore, eWOM was found to mediate the effect of content marketing on product purchase interest. Brand image also has a positive and significant effect on product purchase interest and eWOM, and eWOM can mediate the effect of brand image on product purchase interest.